Strategi penggunaan semula produk berjenama dalam usaha untuk memelihara alam sekitar - Hasnor Sani, Abdul Hamid (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The purpose of the research is to identify the potential of waste and discarded materials and covert them to something valuable such as street furniture. The main objective of this street furniture design is to utilize aluminium can while promoting the corporate identify image of the canned drink and to educate the public the concept of recycle. Finally this study will analyze and identify the most popular brand name for canned drink can and manipulate waste materials and transform into furniture design.